Pro Windows Embedded Compact 7 Producing Device Drivers - Kcholi, Abraham; SpringerLink (Online service) (Berkeley, CA : Apress, 2011)
Windows Embedded Compact 7 is the natural choice for developing sophisticated, small-footprint devices for both consumers and the enterprise. For this latest version, a number of significant enhancements have been made, most notably the ability to run multi-core processors and address more than the 512 MB of memory constraint in previous versions. Using familiar developer tools, Pro Windows Embedded Compact 7 will take you on a deep-dive into device driver development. You$1 (Bll learn how to set up your working environment, the tools that you$1 (Bll need and how to think about developing for small devices before quickly putting theory into practice and developing your own first driver from the ground up. As you delve deeper into the details of driver development, you$1 (Bll learn how to master hardware details, deal with I/O and interrupts, work with networks, and test and debug your drivers ready for deployment$1 (Ball in the company of an author who's been working with Windows CE for more than a decade. Packed with code samples, Pro Windows Embedded Compact 7 contains everything you'll need to start developing for small footprint devices with confidence.s
Keywords: Computer science; Computer Science; Computer Science, general